Family Financial Socialization and Social Media: Their Impact on Educational Investment Decision Among Worker Students, Mediated by Financial Literacy and Internal Locus of Control - Kustitik Kustitik; Heri Pratikto; Hari Wahyono; Dwi Wulandari (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the impact of family financial education and social media on educational investment decisions, with financial literacy and internal locus of control as mediators. The research follows an explanatory design using a survey method. The population consists of 15,530 individuals enrolled in Pamulang University's employee class program. A sample of 375 respondents was selected through proportionate random sampling. Data was collected via an online survey using Google Forms. Partial least squares structural equation modeling (PLS-SEM), analyzed with SmartPLS version 3.0, was employed to estimate the data. The results indicate that social media and family financial socialization both directly and indirectly influence educational investment decisions. However, family financial socialization did not significantly affect financial literacy, and thus could not mediate educational investment decisions. Internal locus of control emerged as the most significant predictor and mediator, suggesting that psychological factors have a stronger influence than financial knowledge. Furthermore, social media was found to play a key role in enhancing students' financial literacy and internal locus of control. Based on these findings, it is recommended that universities implement financial literacy programs for parents to support family financial education, as well as leverage social media to enhance students' locus of control and financial literacy.